Embracing the eye of the Apple: On anthropology, theology and technology - Veldsman, Daniël P. (HTS teologiese studies, 2019)
The playful re-working of the idiomatic expression ‘the apple of my eye’ to the ‘eye/I of my Apple’ provides the answer to the question on technology, emphasising its importance for societies, specifically the South African society, and embodied personhood, and at the same time its determinative contextual character. The answer to the question on technology firstly takes as the vantage point a few personal comments by the author in relation to the question at hand. Secondly, brief remarks on technology and approaches to the question are made before the focus on ethics is explicated and motivated. Lastly, a deep concern is identified and is poignantly described as the probable wicked technologisation of the African soul.